PAR STOCK LINEN YANG IDEAL PADA OPERATIONAL DI DOULOS PHOS THE SHIP HOTEL - Ridha Prayoga, Hetty Yulianti Sihite, Fitriana Baitanu, (JBT (JURNAL BISNIS dan TEKNOLOGI), 2024)
Doulos Phos The Ship Hotel is a resort in Bintan Regency, precisely in the Lagoi industrial area which has a unique theme, namely a cruise ship as an accommodation for guests to stay and feel the sensation of sleeping on a cruise ship. In the operation of the housekeeping department, an ideal number of linen par stock is needed to facilitate the work of room attendants. However, there are several obstacles in high occupancy conditions. This is the aim of the researcher to determine the ideal linen par stock and the inhibiting factors for linen circulation during high occupancy. The research method used in this study is qualitative descriptive and the respondents interviewed were Executive Housekeepers, Front Office Managers and housekeeping staff. The results of this study indicate that there are factors that inhibit linen circulation in the collection of dirty linen, linen inventory and insufficient linen par stock. The conclusion that can be given is the submission of linen purchases that are lacking for operations and the addition of daily workers when high occupancy